Penerapan Flipbook Interaktif Berbasis Model Think Pair Share Upaya Peningkatan Pemahaman Teks Naratif Siswa Kelas V - Yudhistia, Rahma Maulida; Fahlafi, Reza; Rifani, Leny; Purwati, Panca Dewi (YASIN, 2025)
Although the importance of narrative text comprehension in primary education has been highlighted in numerous previous studies, research that specifically examines the integration of interactive digital media with collaborative learning models remains limited. This study aimed to develop and evaluate the effectiveness of the Flipbook Petualangan Naratif assisted by the Think Pair Share (TPS) model based on Problem Based Learning (PBL) in improving narrative text comprehension among fifth-grade elementary school students. A mixed-methods approach with a sequential explanatory design grounded in the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) was employed, involving 22 fifth-grade students of SDN Mangkang Wetan 03 Semarang (21 active students) selected through purposive sampling. Data were collected using a reading comprehension test, observation sheets, student response questionnaires, and semi-structured reflective interviews, and were analyzed using descriptive statistics, paired t-tests, N-Gain analysis, and thematic analysis. The results showed that expert validation placed the product in the “highly feasible” category, with material validity of 86.7% and media validity of 88.6%; quantitatively, there was a significant increase in the mean score from 65.0 (pretest) to 87.5 (posttest) with an N-Gain value of 0.64 (medium–high category), while qualitatively students demonstrated increased active engagement, collaboration skills, and ability to interpret narrative structure and moral messages. These findings contribute to strengthening constructivist learning theory in the context of digital literacy and broaden understanding of effective pedagogy in primary schooling. The study concludes that the Flipbook Petualangan Naratif is an interactive, collaborative, and deep-learning–oriented instructional medium for teaching Indonesian language, and recommends that elementary schools adopt interactive digital media integrated with collaborative models to enhance narrative text comprehension. The implications include theoretical contributions to the literature on digital instructional media in primary education and practical implications for curriculum developers, teachers, and educational technology designers, while also opening avenues for further exploration of flipbook integration with other text genres and the inclusion of gamification elements.